SOME DATA ON THE CONCENTRATION OF HYDROCARBON IN VAN PHON'G - BEN GOI BAY, KHANH HOA PROVINCE (2002 - 2005) - Vinh, Le Thi (Vietnam Journal of Marine Science and Technology, 2007)
During 2002 - 2005, seriously hydrocarbon contamination in Van Phong - Ben Goi was spilled oil in 29, Janumy, 2002. Therefore, hydrocarbon concentration reached 2374 μg/1 in water. However, the residence rime of hydrocarbon from spilled oil in waters was typically about 30 days. Except for this spilled oil event, mean hydrocarbon concentration in waters of Van Phong - Ben Goi bay was 456 μg/1 and its variation ranged from  237 - 629 μg/1. It is possible to say that hydrocarbon pollution is not serious yet. Hydrocarbon concentration in sediments ranged from 208 - 678 μg/1, mean 373 μg/1. It was highest in 2002  because of spilled oil and lowly decreased from 2003 to 2005. The residence time of hydrocarbon from spilled oil in sediments up to 2 years